A Family Based Study of Carbon Monoxide and Nitric Oxide Signalling Genes and Preeclampsia. Issue 1 (7th September 2017) - Bauer, Anna E.; Avery, Christy L.; Shi, Min; Weinberg, Clarice R.; Olshan, Andrew F.; Harmon, Quaker E.; Luo, Jingchun; Yang, Jenny; Manuck, Tracy A.; Wu, Michael C.; Williams, Nicholas; McGinnis, Ralph; et al.
Abstract: Background: Preeclampsia is thought to originate during placentation, with incomplete remodelling and perfusion of the spiral arteries leading to reduced placental vascular capacity. Nitric oxide (NO) and carbon monoxide (CO) are powerful vasodilators that play a role in the placental vascular system. Although family clustering of preeclampsia has been observed, the existing genetic literature is limited by a failure to consider both mother and child. Methods: We conducted a nested case–control study within the Norwegian Mother and Child Birth Cohort of 1545 case‐pairs and 995 control‐pairs from 2540 validated dyads (2011 complete pairs, 529 missing mother or child genotype). We selected 1518 single‐nucleotide polymorphisms (SNPs) with minor allele frequency >5% in NO and CO signalling pathways. We used log‐linear Poisson regression models and likelihood ratio tests to assess maternal and child effects. Results: One SNP met criteria for a false discovery rate Q ‐value <0.05. The child variant, rs12547243 in adenylate cyclase 8 ( ADCY8 ), was associated with an increased risk (relative risk [RR] 1.42, 95% confidence interval [CI] 1.20, 1.69 for AG vs. GG, RR 2.14, 95% CI 1.47, 3.11 for AA vs. GG, Q = 0.03). The maternal variant, rs30593 in PDE1C was associated with a decreased risk for the subtype of preeclampsia accompanied by early delivery (RR 0.45, 95% CI 0.27, 0.75 for TC vs. CC ; Q = 0.02). None of the associations were replicated after correction for multiple testing. Conclusions: This study uses a novel approach to disentangle maternal and child genotypic effects of NO and CO signalling genes on preeclampsia.